2001
DOI: 10.1002/1097-4636(20010615)55:4<503::aid-jbm1043>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Injection molding of chondrocyte/alginate constructs in the shape of facial implants

Abstract: Over one million patients per year undergo some type of procedure involving cartilage reconstruction. Polymer hydrogels, such as alginate, have been shown to be effective carriers for chondrocytes in subcutaneous cartilage formation. The goal of our current study was to develop a method to create complex structures (nose bridge, chin, etc.) with good dimensional tolerance to form cartilage in specific shapes. Molds of facial implants were prepared using Silastic ERTV. Suspensions of chondrocytes in 2% alginate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
204
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(208 citation statements)
references
References 33 publications
3
204
1
Order By: Relevance
“…Alternatively, for the same ECM content compression may also passively increase tissue properties by altering the functional organization and entanglement of the ECM network. A continuous increase in stiffness with time has been observed in several studies, 5,11,36 while others have found an initial increase followed by a plateau. 37,38,40,48 As shown in Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Alternatively, for the same ECM content compression may also passively increase tissue properties by altering the functional organization and entanglement of the ECM network. A continuous increase in stiffness with time has been observed in several studies, 5,11,36 while others have found an initial increase followed by a plateau. 37,38,40,48 As shown in Fig.…”
Section: Discussionmentioning
confidence: 72%
“…2(b) for the model at 56 days. 11 At 12 weeks homogeneous GAG staining was observed which was attributed to alginate degradation. Related to this, the importance of matrix diffusivity has been demonstrated by modulating the degradation behavior of PEG hydrogels.…”
Section: Discussionmentioning
confidence: 95%
“…However, the degradation of these polymers has been reported to cause inflammatory reactions. 3,4 Natural polymer scaffolds and hydrogels, such as alginate 13 and fibrin, 14 are easily molded and have high biocompatibility, 4 but are limited by low stiffness, making them difficult to handle. 15 Chondrocytes encapsulated in alginate and then implanted also become fibrochondrogenic.…”
mentioning
confidence: 99%
“…These methods have been used for engineering of elastic and nonarticular cartilage such as auricle [7,21,41], nose [8,21], and tympanic membrane [17]. Several shaped osteochondral constructs containing articular cartilaginous sections, for phalanx [20,35] and mandibular condyle [1], for example, have been fabricated.…”
Section: Discussionmentioning
confidence: 99%
“…In the molding approach, a mixture of cell and scaffold is placed together into a mold where the scaffold is polymerized, and the shaped construct is cultured. Scaffolds for the molding method are commonly hydrogels, including agarose [19], alginate [8], and photopolymerizable polyethylene glycol derivative [1]. While the results of these studies are promising, the resultant constructs may change from the desired shape due to growth and remodeling, and the surface contours of these constructs have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%